Precision spheres for the Gravity Probe B experiment. (17th November 2015) - Marcelja, F; DeBra, D B; Keiser, G M; Turneaure, J P
Abstract: Spherical gyroscope rotors for a fundamental experiment to test two predictions of General Relativity Theory, geodetic precession and frame dragging, were manufactured out of fused quartz and single-crystal silicon. These rotors required a mass unbalance and asphericity of less than 25 nm (1 μ in), a fractional difference in the moments of inertia of less than 10 −5, and a diameter within 0.5 μ m (20 μ in) of a standard sphere with a diameter of 37.996 mm (1.4959 in). We describe the manufacturing process and the associated metrology.